2007
DOI: 10.1523/jneurosci.2988-07.2007
|View full text |Cite
|
Sign up to set email alerts
|

Mental Simulation of Action in the Service of Action Perception

Abstract: We used the quantitative 14 C-deoxyglucose method to map the activity pattern throughout the frontal cortex of rhesus monkeys, which either grasped a three-dimensional object or observed the same grasping movements executed by a human. We found that virtually the same frontal cortical networks were recruited for the generation and the perception of action, including the primary motor cortex (MI/F1), premotor cortical areas (F2, F5, and F6), the primary (SI) and supplementary (SSA) somatosensory cortex, medial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
95
2
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 85 publications
(108 citation statements)
references
References 40 publications
10
95
2
1
Order By: Relevance
“…Recent imaging studies using the 14 C-deoxyglucose ( 14 C-DG) method demonstrated that the areas activated in the brain of an actor performing a grasping movement and those of an observer watching the performance of the very same movement by another subject are virtually the same. This common neural network involves the forelimb representations of the primary motor and somatosensory cortices; several premotor and cingulate areas; extensive regions of the posterior, lateral, and medial parietal; and the intraparietal cortex (Raos et al, 2004(Raos et al, , 2007Evangeliou et al, 2009). These findings support the notion that we understand observed actions by mentally simulating them.…”
Section: Introductionsupporting
confidence: 69%
See 4 more Smart Citations
“…Recent imaging studies using the 14 C-deoxyglucose ( 14 C-DG) method demonstrated that the areas activated in the brain of an actor performing a grasping movement and those of an observer watching the performance of the very same movement by another subject are virtually the same. This common neural network involves the forelimb representations of the primary motor and somatosensory cortices; several premotor and cingulate areas; extensive regions of the posterior, lateral, and medial parietal; and the intraparietal cortex (Raos et al, 2004(Raos et al, , 2007Evangeliou et al, 2009). These findings support the notion that we understand observed actions by mentally simulating them.…”
Section: Introductionsupporting
confidence: 69%
“…For this reason, we provide quantitative description of the behavior of the monkeys during the critical period of the first 10 min. The oculomotor performance of some of the monkeys, either as instantaneous eye position averaged over all trials or as threedimensional histograms of the dwell time of the line of sight as a function of eye position, during the critical 10 first minutes of the 14 C-DG experiment was presented previously (Raos et al, 2007;Evangeliou et al, 2009). Presently, the oculomotor and skeletomotor performance are briefly reported.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations